2020
DOI: 10.3386/w28104
|View full text |Cite
|
Sign up to set email alerts
|

Sizing up Corporate Restructuring in the COVID Crisis

Abstract: for helpful comments. The views expressed herein are those of the authors and do not necessarily reflect the views of the National Bureau of Economic Research. At least one co-author has disclosed additional relationships of potential relevance for this research. Further information is available online at http://www.nber.org/papers/w28104.ack NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 2 publications
2
16
0
2
Order By: Relevance
“…Hence, their performance in the financial period was good and the public's need for information technology increased. This is in accordance with research conducted by Greenwood et al (2020), one of the results of which was that several companies were able to survive during the Covid-19 pandemic. It also proves the truth of several basic economic theories, namely Engel's curve theory, Giffen's goods theory, marginal substitution theory, and opportunity theory.…”
Section: Results and Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…Hence, their performance in the financial period was good and the public's need for information technology increased. This is in accordance with research conducted by Greenwood et al (2020), one of the results of which was that several companies were able to survive during the Covid-19 pandemic. It also proves the truth of several basic economic theories, namely Engel's curve theory, Giffen's goods theory, marginal substitution theory, and opportunity theory.…”
Section: Results and Analysissupporting
confidence: 92%
“…Fourth, Greenwood et al (2020) concluded a wave of financial difficulties experienced by several companies with the result that some companies are able to survive and several others have the potential to face bankruptcy so that they will face potential liquidation or reorganization downsizing up to acquisitions. Overall, there are two main problems, namely legal problems, court congestion and overliquidation, and small firm failures.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies have shown that higher (lower) bank capital is beneficial (detrimental) for bank shareholders, particularly during crisis episodes(Berger and Bouwman 2013; Cappelletti and others 2020;and Huang, de Haan, and Scholtens 2020). This result is also consistent with a strand of literature showing that credit expansions predict bank equity crash risk(Baron and Xiong 2017;and Gandhi 2018).4 Based on the historical relationship between bankruptcies and unemployment in the United States,Greenwood, Iverson, and Thesmar (2020) show that the pace of business bankruptcy can be expected to increase by 140 percent relative to their 2019 level.©International Monetary Fund. Not for Redistribution…”
supporting
confidence: 75%
“…A Federal Reserve Small Business Credit Survey conducted in 2019 asked small-business bankruptcy counts typically include a large number of small businesses. Greenwood, Iverson, and Thesmar (2020) use a simple model to predict that bankruptcies for businesses of all sizes will rise 140 percent from 2019 levels, although according to this simple model, some of this rise should already be evident. How the bankruptcy status of small businesses actually evolves could have big implications on the economic outlook for both employment and investment: Weak small-business growth hindered the recovery from the Great Recession.…”
mentioning
confidence: 99%